Dedication of the Edwin U. Curtis Memorial, Charles River Esplanade, May 6, 1924 - Belcher, Arnold L. (Tufts Archival Research Center, 2005)
Elevated view of the dedication of this memorial after it was moved from Clarendon Street to the concert area along the Charles River. Massaachusetts Governor Cox is speaking to a large gathering that includes men, women and uniformed officials. Copyprint. Memorial was designed by Guy Lowell. 7 13/16 x 10 11/16 overall 9 x 11 3/16 Photographs